The Shepherd Project: A Case Study of Private Management for Ring-necked Pheasants (Phasianus colchicus) in Montana - Bruce Kania; Frank Stewart (National Quail Symposium Proceedings, 2017)
The Shepherd research farm is headquarters for Floating Island International, a company that produces floating wetlands for water quality and wildlife enhancement. It is also a demonstration site for managing ring-necked pheasants (Phasianus colchicus) on Montana landscapes. Primary goals for the 100-ha farm include an exploration of how agriculture can better integrate with wildlife to achieve a more sustainable landscape. One of the measures of this transition is ring-necked pheasant abundance. During 1998 to 2006, 3 management programs have been implemented: 1) changes in farming methods, 2) targeted habitat development, and 3) predation management. The main change in farming has been a reduction of irrigated annual cropland and pasture from 73% of the land area to 13%. The major crops planted on the site are more diversified and include corn, sorghum-sudan grass, barley, Maximillian sunflower, asparagus, and alfalfa. Other habitat management changes include delayed mowing and incomplete harvest of planted crops. During 7 years, the main predators removed by trapping were raccoon (Procyon lotor), striped skunk (Mephitis mephitis), feral house cat (Felis domesticus), red fox (Vulpes vulpes), and coyote (Canis latrans). Estimates of pheasant abundance were made during the hunting season using change-in-ratio of observed pheasants during male-only harvest. Each year harvest was halted when >75% birds observed were hens. Harvest using this method increased from 14 in 1998 to 207 in 2005. We believe this integrated approach, with its use of less intense agricultural methods, creates a diversified landscape that is beneficial to pheasants and enhances wildlife habitat for a variety of other species.
Keywords: habitat management; harvest; Montana; pheasant